Borreliosis as a cause of myocarditis in pediatric age - Constante, A.D. (2020)
Introduction: Lyme borreliosis (LB) is a zoonosis with worldwide distribution, mainly in the northern hemisphere countries with predominantly cutaneous, articular, cardiac and neuro-psychiatric manifestations. The greater variety of genospecies that cause disease in Europe and the complex laboratory confirmation contribute to the disease underdiagnose in Portugal. Case description: A 17-year-old boy resident in a rural area, with a history of recurrent tonsillitis, initiates cervical pain, odynophagia and fever (39ºC). Blood work showed leukocytosis (11280/uL) and neutrophilia (8569/uL) and CRP 23.6mg/L. Oropharynx antigen screening for SGA and EBV antibodies were negatives but he was discharged with amoxicillin and clavulanic acid. The next day (7th day of disease) he kept fever (38.3°C), initiated a pruritic maculopapular rash on the face, trunk and limbs with palmoplantar involvement and started complaining of thoracic pain that worsened with decubitus. Blood work revaluation indicated increased leukocytosis (14640/uL) and neutrophilia (11040/uL), CRP 142mg/L, VHS 22mm/h. Chest x-ray had a discreet broncho-hilar reinforcement without pleural effusion or cardiomegaly. Electrocardiogram (EKG) in sinus rhythm, with mild infra ST in DIII and aVF, inverted T wave in V1 and V4 and early repolarization pattern in V2-V3. Due to an episode of tachycardia (270 bpm), cardiac markers were accessed and showed troponin 13932pg/mL, CK 436U/L and BNP 373pg/mL, echocardiography showed slight global left ventricular dysfunction and hyperechogenic pericardium without effusion. He was admitted with clindamycin and penicillin and started anti-congestive therapy with carvedilol and enalapril. On the 10th day of disease, of the etiology investigation it was identified by enzyme-linked immunosorbent assay (ELISA) for Borrelia burgdorferi s.l. IgM antibodies positive (53 UA/mL), IgG antibodies negative with confirmatory test-immunoblot IgM positive with bands OspC Bg, p39, p41. Antibiotic therapy was changed to ceftriaxone and doxycycline which he complied with for 8 and 7 days, respectively. On the 20th day of disease cardiac magnetic resonance showed active inflammatory process in the myocardium, but undilated ventricles with preserved global systolic function. Progressive improvement of cardiac markers was noticed, currently with good ventricular function and at the last observation he was asymptomatic from the cardiovascular point of view. Conclusions: LB with myocarditis is a rarity in pediatrics and diagnosis requires a high index of suspicion. When LB cardiac involvement is readily recognized and treated serious complications can be avoided